Communication and language disorders of patients with acquired brain injuries: a retrospective and descriptive study - Cecatto, Rebeca Boltes; Jucá, Sueli Hamada; Nacarato, Maria Inês; Maeda, Fabiana Regina Giacomini; Prieto, Fernanda Franco (Acta Fisiátrica, 2006)
There are few Brazilian studies on communication and language of adults with acquired brain injuries, as well as their relation with motor and cognitive improvement during rehabilitation. This fact, added to the complex evaluation of these conditions, is the reason for this study. The aim of this study was to describe communication disorders in adults with acquired brain injuries and correlate them with biodemographic, clinical and image findings. One hundred and nineteen medical charts of rehabilitation patients seen between October 2002 and 2004 were reviewed. Biodemographic and clinical data were collected together with brain image findings and the pattern of communication disorder according to the speech therapy assessment. Disability was measured by the Functional Independence Measure (FIM). Stroke comprised 74% of the cases, followed by traumatic brain injury (TBI) in 20% and 6% of other etiologies. Fifty-one patients presented with language disorders, whereas 43 had other non-language speech disorders and 25 had no alterations. Aphasia was present in 30.9% of the cases (being 56% of the mixed type), 27.7% had dysarthria, 24.5% were apraxic, 22.3% presented cognitive-communicative impairment, 21.3% had voice disorders, 20.2% had dysphagia, 14.9% had sensorimotor disorders of the mouth, 3.2% had hypoacusia and 1.1% were anomic. There were no associations between gender in the comparison of subgroups with aphasia, linguistic-cognitive disorders, TBI or stroke, as well as no patient presenting right brain dominance for language. The prevalence of aphasia correlated with left side lesions and the linguistic-cognitive disorders with right side lesions and the presence of TBI, with a smaller number of aphasic patients among those with TBI than the remainder of the sample. FIM was associated with language alterations, suggesting that the latter influenced the patients' degree of independence. Conclusion: Communication and its alterations are associated to the patient's other cognitive, motor, socio-cultural and personal alterations, which reinforces the importance of interdisciplinary teams in the functional diagnosis and rehabilitation of patients with acquired brain injuries.